2001
DOI: 10.1046/j.1365-2842.2001.00782.x
|View full text |Cite
|
Sign up to set email alerts
|

Head movement properties during voluntary rapid jaw movement in humans

Abstract: The purpose of this study was to determine whether the start of the synchronized head movement during mandibular movement is evoked by the peripheral reflexes following mandibular movement (i.e. stretch or trigemino-neck reflexes), or, alternatively, is started by pre-programmed central command. Head movement accompanying voluntary rapid jaw opening movement was studied using accelerometers fixed to the upper and lower incisors, as well as electromyographs (EMGs) of the neck muscles. The direction of head acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
0
13
0
2
Order By: Relevance
“…Functional coupling occurs between the upper and lower limbs during daily ambulatory movements such as walking, running and swimming (see, for example, DEFIBAUGH (1964), DONKER et al (2001), WANNIER et al (2001) andZEHR andHARIDAS (2003)). In the maxillofacial areas, functional coupling also occurs between the jaw and head during jaw opening and closing (TORISU et al, 2001;YAMABE et al, 1999;ZAFAR, 2000;ZAFAR et al, 2000) and has been suggested to occur between the head and trunk (MIYAOKA et al, 2004;YAMABE et al, 1999), but functional coupling needs to be evaluated quantitatively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Functional coupling occurs between the upper and lower limbs during daily ambulatory movements such as walking, running and swimming (see, for example, DEFIBAUGH (1964), DONKER et al (2001), WANNIER et al (2001) andZEHR andHARIDAS (2003)). In the maxillofacial areas, functional coupling also occurs between the jaw and head during jaw opening and closing (TORISU et al, 2001;YAMABE et al, 1999;ZAFAR, 2000;ZAFAR et al, 2000) and has been suggested to occur between the head and trunk (MIYAOKA et al, 2004;YAMABE et al, 1999), but functional coupling needs to be evaluated quantitatively.…”
Section: Discussionmentioning
confidence: 99%
“…Motor activities that have been recorded with accelerometers include not only daily ambulatory movements, such as walking and running (BoUTEN et al, 1997;FLAVEL et al, 2002;GILBERT et al, 1984;MAKIKAWA et al, 2001;MURAKAMI and MAKIKAWA, 1997;TULEN et al, 2000;WESTERTERP, 1999), but also much smaller movements in maxillofacial areas, such as jaw opening and closing (TORISU et al, 2001;YAMABE et al, 1999;ZAFAR, 2000;ZAFAR et al, 2000). The present study was designed to characterise head movements together with trunk drift recorded with accelerometers in unrestrained subjects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relationship between stomatognathic-and head-neck systems Functional or physiological significance of the coupling between the stomatognathic system and the head-neck system has been frequently reported (Hellström et al, 2000;Zeredo et al, 2002;Eriksson et al, 1998;Torisu et al, 2001, Koolstra and Eijden, 2004). Dessem and Luo (1999) observed a neural projection from masticatory-muscle spindle afferents to the cervical spinal cord in rats by combining retrograde and intracellular neural labeling.…”
Section: The Emg Inhibition Is Followed By An Excitatory Periodmentioning
confidence: 99%
“…Accelerometers have been used to measure a wide range of physiological characteristics [3][4][5][6][7], with emphasis on motor activities [8][9][10][11][12], such as walking and running [5,6,[13][14][15][16][17][18], as well as on some studies of small movements, such as those in the temporomandibular region, mainly related to jaw opening and closing movements [19][20][21], in the characterization of respiratory disorders, such as apneas [3], [22,23], in the study of human body impact and vibration [24,25], its characterization posture [26,27], and movements performed during sleep [28,29].…”
Section: Basic Concepts On Accelerometrymentioning
confidence: 99%